Status epilepticus in the elderly: epidemiology, clinical aspects and treatment - Telma M.R. de Assis; Gersonita Costa; Aroldo Bacellar; Marco Orsini; Osvaldo J.M. Nascimento (MDPI AG, 2012)
The aim of the study was to review the epidemiology, clinical profile and discuss the etiology, prognosis and treatment options in patients aged 60 years or older presenting with status epilepticus. We performed a systematic review involving studies published from 1996 to 2010, in Medline/PubMed, Scientific Electronic Library on line (Scielo), Latin-American and Caribbean Center of Health Sciences Information (Lilacs) databases and textbooks. Related articles published before 1996, when relevant for discussing epilepsy in older people, were also included. Several population studies had shown an increased incidence of status epilepticus after the age of 60 years. Status epilepticus is a medical and neurological emergency that is associated with high morbidity and mortality, and is a major concern in the elderly compared to the general population. Prompt diagnosis and effective treatment of convulsive status epilepticus are crucial to avoid brain injury and reduce the fatality rate in this age group.